Long-Term Evaluation of Ifosfamide-Related Nephrotoxicity in Children - Odile Oberlin; Oumaya Fawaz; Annie Rey; Patrick Niaudet; Vita Ridola; Daniel Orbach; Christophe Bergeron; Anne Sophie Defachelles; Jean‐Claude Gentet; Claudine Schmitt; Hervé Rubie; Martine Münzer; et al. (2009)
Ifosfamide is widely used in pediatric oncology but its nephrotoxicity may become a significant issue in survivors. This study is aimed at evaluating the incidence of late renal toxicity of ifosfamide and its risk factors.Of the 183 patients prospectively investigated for renal function, 77 treated for rhabdomyosarcoma, 39 for other soft tissue sarcoma, 39 for Ewing's sarcoma, and 28 for osteosarcoma were investigated at least 5 years after treatment. No patients had received cisplatin and/or carboplatin. Glomerular and tubular functions were graded according to the Skinner system.The median dose of ifosfamide was 54 g/m(2) (range, 18 to 117 g/m(2)). After a median follow-up of 10 years, 89.5% of patients had normal tubular function, and 78.5% had normal glomerular function rate (GFR). Serum bicarbonate and calcium were normal in all patients. Hypomagnesemia was observed in 1.2% and hypophosphatemia in 1%. The tubular threshold for phosphate was reduced in 24% of the patients (grade 1 in 15%, grade 2 in 8%, and grade 3 in 0.5%). Glycosuria was detected in 37% of the patients but was more than 0.5 g/24 hours in only 5%. Proteinuria was observed in 12%. Ifosfamide dose and interval from therapy to investigations were predictors of tubulopathy in univariate and multivariate analysis. In a multivariate analysis, an older age at diagnosis and the length of interval since treatment had independent impacts on the risk of abnormal GFR.Renal toxicity is moderate with a moderate dose of ifosfamide. However, since it can be permanent and can get worse with time, repeated long-term evaluations are important, and this risk should be balanced against efficacy.